Bahasa nonverbal sebagai konteks dalam pembelajaran BIPA: kajian pragmatik edukasional - Pranowo Pranowo (Badan Pengembangan dan Pembinaan Bahasa, 2019)
Non-verbal language learning as a context of Indonesian as foreign language learning needs serious attention because, in addition to learning verbal writing language, they also learn spoken language and cultural background. Therefore, learning must integrate an educationally linguistic approach with educational pragmatic words. Educational linguistic approaches in its nature are teaching the structure of language and its meaning, while a pragmatic approach or communicative approach is, in fact, the teaching of the use of languages and the context of its usage. The problem in this article is